Pemanfaatan Media Digital dalam Pembelajaran - Kuntari, Septi (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
In the current era of globalization, technological development is very fast, especially in the form of digital media which is widely used by the community, especially in the field of education. Digital media used in the learning process provides benefits to support the achievement of learning outcomes. Proper utilization of digital media and the existence of strategies in the application of appropriate digital media are considered effective in the learning process. At this time, students are considered a generation that includes digital literacy where they are accustomed to using digital media in their daily lives, especially in the school environment. However, there are still many students out there who still cannot fully utilize digital media due to various constraints, especially limitations in access to technology. The purpose of writing this article is to explain the utilization of digital media in the world of education, especially where digital media can facilitate the presentation of material by educators and add insight into knowledge for educators and students.